The phenomenon of code mixing among KLM students: its factors and effects - Nor Zailan, Nor Athirah Mursyidah; Mohd Ismath, Nurul Hanilah (Kulliyyah of Languages & Management (KLM), International Islamic University Malaysia, Edu Hub Pagoh, 84600 Muar, Johor Darul Takzim., 2021)
The phenomenon of code-mixing is one of the linguistic phenomena which occurs among bilinguals and multilinguals where it includes the use of words or phrases from certain language in other language in which the speaker is using. This phenomenon is still developing and spreading widely in the world which attracts the attention of the researcher in conducting this scientific study. This study aims to discover the perceptions of Arabic Language for International Communication students in Kulliyyah of Languages and Management towards the phenomenon of code-mixing, as well as to identify the most important factors which lead to this phenomenon together with its effects. This study uses descriptive approach where quantitative and analytical method is applied by distributing questionnaire to all students from different level of studies and analysing it through Statistical Package for the Social Sciences (SPSS) software. Research results indicate that code-mixing occurs naturally and is regarded as a common phenomenon among students, and there are many factors which lead to such phenomenon. Finally, the phenomenon of code-mixing affects students both positively and negatively, mostly positively.